Correction to: Psychological and somatic distress in Chinese outpatients at general hospitals: a cross-sectional study - Xiong, Nana; Schäfert, Rainer (Annals of general psychiatry, 2018)
Unfortunately, after publication of this article [1], it was noticed that the affiliation of Rainer Schaefert is incorrectly displayed as, “Department of General Internal Medicine and Psychosomatics, University Hospital Heidelberg, Heidelberg, Germany”. The correct affiliation should read, “Department of Psychosomatics, Medical Division, University Hospital Basel, Basel, Switzerland” and can be seen in the author details of this correction.